Characteristic features of cognitive, affective and daily living functions of late‐elderly dementia. Issue 4 (8th May 2015) - Hishikawa, Nozomi; Fukui, Yusuke; Sato, Kota; Kono, Syoichiro; Yamashita, Toru; Ohta, Yasuyuki; Deguchi, Kentaro; Abe, Koji
Abstract : Aims: The world is rapidly aging, and is facing an increase of late‐elderly dementia patients. It is important to investigate the characteristic features of late‐elderly dementia in a super‐aged country. Methods: We examined 1554 patients with cognitive decline in Department of Neurology, Okayama University Hospital, Okayama, Japan, divided into three subgroups according to the age: young‐elderly (age ≤64 years), middle‐elderly (age 65–74 years) and late‐elderly (age 75 years), and investigated the cognitive, affective and activities of daily living functions (ADL), especially in late‐elderly patients compared with young‐elderly and middle‐elderly patients. Results: Among 1554 patients, Alzheimer's disease dominated at 62%, and age‐dependently increased up to 69% in the late‐elderly group. The total scores of four cognitive tests were significantly worse with aging for specific subscales of orientation, recall, visual retention, word fluency and so on. In contrast, total scores of the affective tests showed only an increase in the apathy scale in the late‐elderly group. Each subgroup showed depressive/depression in 63.2–55.2%, and apathy in 44.2–54.8%. Furthermore, instrumental ADL items significantly deteriorated in the late‐elderly group, which statistically correlated with Mini‐Mental State Examination score. Conclusions: These results show that the late‐elderly group is characterized by significant cognitive declines, increasing apathy, and instrumental ADL decrease. The cognitive decline may be related to such affective and ADL declines.Geriatr Gerontol Int 2016; 16: 458‐465.